The effect of person-organization fit on affective commitment with job satisfaction as a mediating variable - Giansa Viola (Universitas Negeri Padang, 2021)
This study aims to (1) determine and analyze the effect of person-organization fit on affective commitment (2) to determine and analyze the effect of person-organization fit on job satisfaction (3) to determine and analyze the effect of job satisfaction on affective commitment (4) to be able to know and analyze the effect of job satisfaction that mediates person-organization fit on affective commitment. This research is causal. The population in this study were all employees of the Whiz Prime Hotel Khatib Sulaiman Padang, with a total of 51 people. The sampling technique used total sampling where the number of samples was the same as the population, namely 51 people. Collecting data using a questionnaire with a Likert scale. The analysis technique used is through the SmartPLS software. The results of this study found that: (1) person-organization fit has a positive and significant effect on the affective commitment of the employees of Hotel Whiz Prime Khatib Sulaiman Padang. (2) person-organization fit has a positive and significant effect on job satisfaction of employees of Hotel Whiz Prime Khatib Sulaiman Padang. (3) Job satisfaction has a positive and significant effect on the affective commitment of employees of Hotel Whiz Prime Khatib Sulaiman Padang. (4) person-organization fit has a positive and significant effect on employee affective commitment with job satisfaction as a mediating variable for employees of Hotel Whiz Prime Khatib Sulaiman Padang.